2012
DOI: 10.1002/smll.201102223
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of Molecular Orientation on the Intensity of Chemical Enhancement Using Graphene‐Enhanced Raman Spectroscopy

Abstract: A rational approach to investigate the effect of molecular orientation on the intensity of chemical enhancement using graphene-enhanced Raman spectroscopy (GERS) is developed. A planar molecule, copper phthalocyanine (CuPc), is used as probe molecule. Annealing allows the CuPc molecule in a Langmuir-Blodgett film to change orientation from upstanding to lying down. The UV-visible absorption spectra prove the change of the molecular orientation, as well as the variation of the interaction between the CuPc molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
128
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 42 publications
(29 reference statements)
6
128
0
Order By: Relevance
“…2014, 7(9): 1271-1279 molecule orientation [3], electronic energy levels [4][5], graphene thickness [6], and the incident conditions [7], were then implemented, and the enhancement mechanism was attributed solely to a chemical mechanism (CM). However, one of the most commonly used Raman probes, rhodamine 6G (R6G), yielded confusing results about the Raman enhancement effect on grapheme [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…2014, 7(9): 1271-1279 molecule orientation [3], electronic energy levels [4][5], graphene thickness [6], and the incident conditions [7], were then implemented, and the enhancement mechanism was attributed solely to a chemical mechanism (CM). However, one of the most commonly used Raman probes, rhodamine 6G (R6G), yielded confusing results about the Raman enhancement effect on grapheme [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Various experimental studies have been carried out to unravel the SERS enhancement mechanism of graphene: Ling et al has shown that the enhancement depends on the orientation of the molecules in its "first-layer" vicinity; 14,15 Xu et al has further shown that SERS enhancement of graphene can be modulated by tuning its Fermi level with a graphene field-effect transistor (GFET) device. 16,17 These studies suggest that SERS enhancement of graphene is a CE effect.…”
mentioning
confidence: 99%
“…5 In SERS, it is widely believed that there are two contributions to its enhancement: an electromagnetic mechanism (EM) through intense enhancement of the localized electromagnetic fields around metallic nanostructures [6][7][8][9][10] and a chemical mechanism (CE) through a combination of metal-molecule chemical interactions. [11][12][13] Various experimental studies have been carried out to unravel the SERS enhancement mechanism of graphene: Ling et al has shown that the enhancement depends on the orientation of the molecules in its "first-layer" vicinity; 14,15 Xu et al has further shown that SERS enhancement of graphene can be modulated by tuning its Fermi level with a graphene field-effect transistor (GFET) device. 16,17 These studies suggest that SERS enhancement of graphene is a CE effect.…”
mentioning
confidence: 99%
“…For example, CuPc molecule will be in lying-down position after annealing, which results in a molecular orientation that isoindole group is in parallel with graphene surface. 1530 cm −1 mode, which represents symmetric stretching of isoindole groups of CuPc molecules, has highest enhancement than other vibrational modes of CuPc after annealing [39].…”
Section: Raman Enhancement Mechanism Of Two-dimensional Materialsmentioning
confidence: 94%
“…The graphene electrons involvement in the Raman scattered process can enhance the electron-phonon coupling and thus induce the enhancement of the Raman signals. When a vibrational mode involves the lone pair or electrons, which has stronger coupling with graphene [20,39], the vibrational mode with particular molecular orientations could have highest Raman enhancement, following the SERS selection rules. For example, CuPc molecule will be in lying-down position after annealing, which results in a molecular orientation that isoindole group is in parallel with graphene surface.…”
Section: Raman Enhancement Mechanism Of Two-dimensional Materialsmentioning
confidence: 99%